CSIG-29. EMPLOYING THE ZIKA VIRUS AS ONCOLYTIC VIROTHERAPY AGAINST PAEDIATRIC NERVOUS SYSTEM CANCER CELLS. (14th November 2022) - Sherwood, Matthew; Kaid, Carolini; Mitsugi, Thiago; Zhou, Yilu; Wang, Yihua; Skipp, Paul; Gray, Juliet; Okamoto, Oswaldo; Ewing, Rob
Abstract: BACKGROUND: Malignant paediatric nervous system tumours, such as medulloblastoma, ATRT and high-risk neuroblastoma commonly harbour tumour cells with stem-like features which are highly tumorigenic and resistant to conventional therapies. These tumours can exhibit high lethality and may result in severe sequelae that significantly affect paediatric patients' quality of life. Oncolytic virotherapy exploits viruses that preferentially infect and destroy tumour cells. These viruses present a unique advantage in targeting highly heterogeneous cancers as they possess a secondary mechanism of action, through which they induce an anti-tumoral immune response. The Zika virus (ZIKV) is capable of infecting and destroying aggressive human paediatric brain tumour and neuroblastoma cells in vitro . ZIKV effectively reduces brain tumour size in mice (xenograft model) and canines (naturally occurring) and can induce an immune response against canine brain tumours. METHODS: Employing global expression omics profiling of ZIKV infection and mapping of viral protein-host protein interactions, we aim to elucidate the mechanisms which underpin ZIKVs therapeutic properties, both at the molecular and cellular pathway levels. RESULTS: Through extensive transcriptome profiling of ZIKV-infected paediatric brain tumour, neuroblastoma and NPCs, we have identified a variety of pathways which are involved in the ZIKV oncolytic response in the tumour cells and its neuro-dysregulation of NPCs. Despite both brain tumour and neuroblastoma cells undergoing ZIKV-induced oncolysis, we observed there to be a heterogeneous response within these different tumour cells at the molecular level to lead to oncolysis. Additionally, the infected tumour cells demonstrate elevated immune system profiles which alludes to the immune response that ZIKV may raise within the patient's body against the paediatric tumour. Analysing our findings alongside the neuro-dysregulation we observe in our ZIKV-infected NPCs is allowing us to build a safety profile for employing a ZIKV-based therapy, whilst contributing to the growing knowledge of Congenital ZIKV Syndrome.